Picture recognition improves with subsequent verbal information - Wiseman, S; MacLeod, C M; Lootsteen, P J (Journal of experimental psychology. Learning, memory, and cognition, 1985)
In three experiments, subjects studied photographs presented alone or followed by a descriptive sentence. The sentence provided additional information not available in the picture. Subsequent yes-no recognition tests for the pictures demonstrated better memory for those pictures that had been followed by descriptive sentences. Experiment 1 showed that described pictures were remembered better regardless of whether comparison was to undescribed pictures presented in immediate succession or to undescribed pictures followed by a blank period equal in duration to the descriptive sentence. Experiment 2 demonstrated that although both unrelated and related sentences aided picture recognition, related sentences were significantly more helpful. Experiment 3 revealed that increasing the amount of related information (low, medium, and high) had no differential effect on picture recognition. Three explanations of these results are considered: integration of the sentence with the picture, formation of a semantic representation in addition to the pictorial one, and elaboration of the pictorial representation initiated by the sentence. Taken together, the findings seem most consistent with the elaboration account--A post-picture sentence improves attention to and perhaps rehearsal of the representation of the picture following its display.